CD3zeta-mediated modulation of TCR signaling: a novel strategy for neuroprotection in retinal ganglion cell degeneration - Xu, Kexin; Yang, Ning; Yu, Lu; Wang, Zhiyi; Zhang, Ningzhi; Cao, Wenye; Xing, Yiqiao (Frontiers in Cell and Developmental Biology, 2025)
PurposeGlaucoma, a leading cause of irreversible blindness, involves complex mechanisms beyond elevated intraocular pressure (IOP), including immune signaling dysregulation. This study focused on the role of the T-cell receptor (TCR) signaling pathway, particularly the CD3ζ chain, in retinal ganglion cell (RGC) degeneration and explored its potential as a neuroprotective target via immune modulation.MethodsA mouse optic nerve crush model was used to mimic glaucomatous neurodegeneration. CD3ζ knockdown was achieved using adeno-associated virus serotype 9 encoding short hairpin RNA. Retinal tissues were evaluated via immunofluorescence, Western blotting, and RT-qPCR to analyze the survival and death of RGCs and activation of key signaling pathways, including the MAPK and NF-κB pathways. Changes in inflammatory cytokine profiles were assessed to examine the broader impact of TCR modulation.ResultsCD3ζ knockdown significantly improved RGC survival by reducing apoptosis and necroptosis. The neuroprotective effect of CD3ζ knockdown was accompanied by the restoration of MAPK signaling, specifically the phosphorylation of ERK and p38, and attenuation of NF-κB activation, indicated by decreased p65 phosphorylation. Furthermore, CD3ζ knockdown reduced the levels of proinflammatory mediators (IL-1β, TNF-α, and MMP-9) and increased that of the anti-inflammatory cytokine IL-10, creating a retinal microenvironment conducive to neuroprotection.ConclusionThis study demonstrates that CD3ζ plays a critical role in immune-mediated neurodegeneration in glaucoma. CD3ζ knockdown promotes RGC survival by modulating MAPK and NF-κB signaling pathways and regulating apoptosis and inflammation. These findings underscore the therapeutic potential of targeting TCR signaling to complement existing IOP-lowering treatments, offering a novel approach to preserving visual function in glaucoma.